Vertical distribution of the Asian tropopause aerosols detected by CALIPSO. (October 2019) - Niu, Hewen; Kang, Shichang; Gao, Wanni; Wang, Yuhang; Paudyal, Rukumesh
Abstract: Characterizing the vertical distribution of aerosol optical properties is crucial to reduce the uncertainty in quantifying the radiative forcing and climate effects of aerosols. The analysis of four-year (2007–2010) Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) lidar measurements revealed the existence of tropospheric aerosol layers associated with the Asian summer monsoon. The measurements of five typical aerosol optical and microphysical parameters were used to explore the properties, spatial/vertical distributions, annual evolution of tropopause aerosols over the South Asia region. Results extracted from various latitude-height and longitude-height cross sections of aerosol extinction coefficient at 532 and 1064 nm, backscatter coefficient at 532 nm, and depolarization ratio at 532 nm demonstrated that a large amount of aerosols vertically extended up to the tropopause (12 km) during the monsoon season over the north Arabian Sea, India, north Bay of Bengal, and equatorial Indian Ocean, finally reaching the southeast of the Tibetan Plateau. Convective transport associated with Asian summer monsoon is an important factor controlling the vertical distribution of tropopause aerosols. The evolution of aerosol scattering ratio at 532 nm indicated that from equatorial Indian Ocean to South Asia, there exists an upward tilting and ascending structure of the aerosols layer during the monsoon season, which typically indicates enhanced aerosols over the Asian monsoon region. Information on aerosol size distribution and detailed composition are needed for better understanding the nature and origin of this aerosol layer. Enhancement of the tropopause aerosols should be considered in the future studies in evaluating the regional or global climate systems. Further satellite observations of aerosols and in-situ observations are also urgently needed to diagnose this aerosol layer, which likely originate from anthropogenic emissions. Graphical abstract: Image 1 Highlights: Aerosol optical and microphysical parameters have been used to specify the vertical distribution. CALIPSO lidar measurements have revealed the existence of tropospheric aerosol layers. There exists a tilting and ascending structure of aerosols layer during the monsoon season.